The exposure of a fresh fruit and vegetable supply chain to global water-related risks. Issue 6 (18th August 2018) - Hess, Tim; Sutcliffe, Chloe
ABSTRACT: We have combined estimates of the UK's supply of fresh fruit and vegetables (1996 – 2015) with estimates of water requirements and water scarcity in producing countries, to identify where the supply is exposed to physical, regulatory and reputational water risks and how this has changed over time. Some 76% of the freshwater consumed in the supply of fresh fruit and vegetables to the UK is withdrawn overseas. The supply chain is particularly exposed to water risks in Spain, Egypt, South Africa, Chile, Morocco, Israel and Peru. Exposure has increased over time.